Artes plásticas infantiles - Alcívar Flores, Patricia Del Pilar (2017)
The Plastic Arts for Children project is presented with the purpose of contributing to stimulate the development of skills and abilities in the initial education through the implementation of techniques and methodologies for the improvement of the motor spheres. The research was based on a general diagnosis about the psychomotor level of children in the "Provincial Council of Cotopaxi" School of Basic Education in La Maná canton, which began by recognizing the environment in which they develop. The school has 156 students, 79 girls and 77 children, who are distributed for years in an average of 26 students per parallel. Research is supported by the application of various methods such as descriptive, analytical, synthetic, observation and techniques such as surveys. The theoretical basis was structured with the conceptualization of different bibliographical components such as art and its characteristics, artistic expressions, plastic arts, their importance and incidence in children's education, besides the observation, manipulation and exploration of each of the themes and subtopics oriented to the development of the fine motor for the integral formation of the student. For the collection of information, surveys were developed for parents and teachers and for students a checklist. The information obtained allowed to conclude that the academic training of the majority of teachers at the pre-primary level is limited or lacking experience, which has influenced to a certain extent in a negative way in the process of teaching learning and psychomotor development. For the above mentioned, it is proposed to develop blocks of activities with methodologies to train teachers in the management and application of techniques of children's plastic arts, which facilitates the educational work while being friendly to nature and develop their fine motor skills.